THE EFFECT OF PERCEPTION ON HIGH RISK TAKING BEHAVIOR AND VOCABULARY MASTERY TOWARDS STUDENTS’ SPEAKING SKILL - Lupthi Dwi Pranata; Supeno Supeno (INFERENCE: Journal of English Language Teaching, 2021)
Abstract: This research aims to determine the effects of perception on high risk-taking behavior and vocabulary masteries on the students’ speaking skills. The methodology used in this research is a survey method. The hypothesis test is 1) there are any significant effects of perception on high risk-taking behavior and vocabulary mastery jointly towards the students’ speaking, Sig. 0,000<0.05 and Fo=38.336. Perception on high risk-taking behavior and vocabulary masteries variables together accounted for 48,1% of the variable students’ speaking skill. 2)there is a significant effect of perception on high risk-taking behavior towards the students’ speaking, Sig.= 0.002<0.05 and ?o=3,269. Perception high risk-taking behavior accounted for 18,47 % of the increase of the students’ speaking skills. 3)there is a significant effect of the vocabulary mastery towards the students’ speaking, Sig.=0,000<0,05 and to=7.224. Variable vocabulary mastery accounted for 29,39% of the increase of the students’ speaking skills. In conclusion, teachers are recommended to enhance students’ perception of high-risk behavior and vocabulary masteries to improve their speaking skills.Keywords: perception, high risk-taking behavior, vocabulary mastery, speaking skill